178k views
4 votes
Factor the following trinomials.
x²-6x+4

1 Answer

4 votes

Answer:


(x-3-√(5))(x-3+√(5))

Explanation:

Start with the discriminant of the trinomial


x^2-6x+4

The discriminant is


D=b^2-4ac=(-6)^2-4\cdot 1\cdot 4=36-16=20

Now, find the roots of the trinomial using the quadratic formula


x_(1,2)=(-b\pm √(D))/(2a)=(-(-6)\pm √(20))/(2\cdot 1)=(6\pm2√(5))/(2)=3\pm √(5)

So, the factored form of the trinomial is


(x-(3+√(5)))(x-(3-√(5)))=(x-3-√(5))(x-3+√(5))

User Dixit Panchal
by
5.2k points